2(v-3)=9v+36

Simple and best practice solution for 2(v-3)=9v+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(v-3)=9v+36 equation:


Simplifying
2(v + -3) = 9v + 36

Reorder the terms:
2(-3 + v) = 9v + 36
(-3 * 2 + v * 2) = 9v + 36
(-6 + 2v) = 9v + 36

Reorder the terms:
-6 + 2v = 36 + 9v

Solving
-6 + 2v = 36 + 9v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-9v' to each side of the equation.
-6 + 2v + -9v = 36 + 9v + -9v

Combine like terms: 2v + -9v = -7v
-6 + -7v = 36 + 9v + -9v

Combine like terms: 9v + -9v = 0
-6 + -7v = 36 + 0
-6 + -7v = 36

Add '6' to each side of the equation.
-6 + 6 + -7v = 36 + 6

Combine like terms: -6 + 6 = 0
0 + -7v = 36 + 6
-7v = 36 + 6

Combine like terms: 36 + 6 = 42
-7v = 42

Divide each side by '-7'.
v = -6

Simplifying
v = -6

See similar equations:

| 8u+32+3u=-23 | | 2x=5(2-4x) | | 1/sinh(x) | | ln(x^2-25)=10+ln(75) | | X^5/15×X^7/15 | | 3(a+2)+2(4+b)= | | (k-1)x^2-2kx+k^2=0 | | -2v+8(v-3)=-6 | | (k+1)x^2-2kx+k^2=0 | | 7+2x=8-5(3+x) | | 7x+7x+6b= | | 6+w=-12+2w | | -3(y+6)=-45 | | 8a-2b+4-3b+a-3= | | y-9=0.3(x+2) | | 4cos^2x-4cosx-3=3 | | -9x(x+6)=3(x+18) | | a+c=b+c | | -10n+10=-12n | | y-9=0.3(x+9) | | y-7=-3(x-1) | | 3x(4x-8)(x+5)=0 | | (2xlnx-x)/lnx^2=0 | | 13x+4(2x-1)=5(x+2) | | 3a+6b-5a+2b= | | 9b-3b+11=23 | | 8/360=40/x | | 10(x+4)-9(x-3)=8 | | 3(x-7)=x+13 | | 2.27-s/4=2 | | 3(x-7)=x+133 | | 4=2y-3 |

Equations solver categories